The Mediating Role of Financial Performance in Foreign Ownership on Stock Price Volatility of Technology Companies on the BEI - Kariska Try Rahmatika Nggolon; Muhammad Yunus Kasim; Vitayanti Fattah; Erwan Sastrawan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the mediating role of financial performance in the relationship between foreign ownership and stock price volatility of technology companies listed on the Indonesia Stock Exchange for the period 2020–2024. Using a quantitative causal approach and secondary data, the study analyzed a sample of 17 companies via panel data regression using the Common Effect Model, path analysis, and the Sobel test. The results show that foreign ownership has a significant negative effect on stock price volatility and a significant positive effect on financial performance, as measured by both ROA and ROE. Financial performance does not have a significant effect on stock price volatility. Furthermore, financial performance does not mediate the relationship between foreign ownership and stock price volatility.